2021
DOI: 10.1200/go.21.00139
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of COVID-19 in Solid Organ Malignancies: Experience From a Tertiary Cancer Center in Eastern India

Abstract: PURPOSE The COVID-19 pandemic has imposed a unique challenge to oncology patients. Outcome data on COVID-19 in patients with cancer from the Indian subcontinent are scarce in the literature. We aimed to evaluate the outcome of patients with COVID-19 on active systemic anticancer therapy. MATERIALS AND METHODS This is a retrospective study of patients with solid organ malignancies undergoing systemic therapy with a diagnosis of COVID-19 between March 2020 and February 2021. COVID-19 was diagnosed if a reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…When compared with other real-world experiences of the COVID-19 disease in cancer patients, our study is unique in comparing the characteristics of both waves. The most common malignancy encountered in our study was of the lungs followed by GIT and breast, which conforms with contemporary studies by Roy et al and CCC-19 literature, 7,16 however differs from the UK Coronavirus Cancer Monitoring Project (UKCCMP) data. 17 The case fatality rate in an unselected Indian population was 1.9% 8 ; however, in cancer patients, it was reported to be 6.5% in the first wave from a study in cancer patients in India.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When compared with other real-world experiences of the COVID-19 disease in cancer patients, our study is unique in comparing the characteristics of both waves. The most common malignancy encountered in our study was of the lungs followed by GIT and breast, which conforms with contemporary studies by Roy et al and CCC-19 literature, 7,16 however differs from the UK Coronavirus Cancer Monitoring Project (UKCCMP) data. 17 The case fatality rate in an unselected Indian population was 1.9% 8 ; however, in cancer patients, it was reported to be 6.5% in the first wave from a study in cancer patients in India.…”
Section: Discussionsupporting
confidence: 90%
“…There have been studies from India as well as the rest of the world depicting the outcomes and mortality of cancer patients affected with COVID-19. 5,6 Roy et al reported 145 patients of solid organ malignancies, of which 22 (15%) patients succumbed, 7 whereas Mehta et al reported a glaringly high CFR of 28% in cancer patients when compared to match noncancer population (14%). 8 With the vaccine roll-out drives in full swing across the world, the glaring truth is that this subgroup of patients were excluded from all vaccine trials; hence, the efficacy in the setting of malignancy remained elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The median duration to negative RT-PCR test in cancer patients after COVID infection was 16 days in 88 Indian patients with solid organ cancers. 23 To understand the effect of delaying cancer treatment in view of avoiding COVID infection, a Markov-model-based analysis was conducted for women at risk of cervical cancer in India. It was seen that there was a lifetime increase of about 795 to 2160 (2.52-3.80%) cervical cancer related deaths due to delay in treatment ranging from 9 weeks to 6 months, respectively.…”
Section: Acceptable Delay In Gynecologic Cancer Surgerymentioning
confidence: 99%
“… 22 The median duration to negative RT-PCR test in cancer patients after COVID infection was 16 days in 88 Indian patients with solid organ cancers. 23 …”
Section: Introductionmentioning
confidence: 99%